Sustainable development using renewable energy technology - Østergaard, Poul Alberg; Duic, Neven; Noorollahi, Younes; Mikulcic, Hrvoje; Kalogirou, Soteris A. (My University, 2020)
This article present a review of the status of research within the exploitation of renewable energy sources with a focus on the status of technologies exploiting renewable energy sources, a status of the assessment of the availability of renewable energy sources and the status on the research into the types of systems, that can integrate renewable energy sources. In terms of technologies and resources, wind and wave power resources, wind technology, geothermal energy, solar heating, cooling and electricity and salinity gradient technologies are reviewed. Lastly, system integration, impacts and environmental performance of energy systems are assessed. The review takes a starting point in work presented at the conference series on Sustainable Development of Energy, Water and Environmental Systems (SDEWES), published in Special Issues in various journals and puts this work into a wider context.
Keywords: Wind power; Wave power; Solar heating; Cooling and power; Geothermal energy; Salinity gradient; System impacts